Strategi Lembaga Pendidikan Islam dalam Membentuk Karakter Siswa di Era Digital - Nurhabibi, Nurhabibi; Arifannisa, Arifannisa; Ismail, Diauddin; Kuswandi, Dedi; Anggraeni, Aprillia Fentika Dewi Gita; Aji, Yunita Abdullah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The digital era has brought significant changes to society, particularly in the behavior and morality of the younger generation. The development of information and communication technology, especially social media, has become an inseparable part of students' lives, while simultaneously presenting new challenges for Islamic educational institutions in fulfilling their role in character formation. This study aims to examine the strategies implemented by Islamic educational institutions in shaping students’ character in the digital age, as well as to evaluate their effectiveness in facing contemporary challenges. The research method used is a qualitative approach with a literature review as the main data collection technique. The findings show that the implemented strategies include the integration of Islamic digital education, exemplary teacher models, the application of technology in teaching Islamic values, the empowerment of digital-based religious activities, and the strengthening of parental and teacher supervision and guidance roles. Although some institutions have successfully implemented these strategies, challenges such as a lack of digital literacy, weak supervision, and limited resources remain significant obstacles. This study recommends the importance of collaboration among educational institutions, families, and society in formulating policies and character-building innovations that align with technological developments. These findings are expected to contribute to strengthening an Islamic education system that is responsive to the dynamics of the digital era.ABSTRAKEra digital telah membawa perubahan besar dalam kehidupan masyarakat, khususnya dalam perilaku dan moral generasi muda. Perkembangan teknologi informasi dan komunikasi, terutama media sosial, telah menjadi bagian tak terpisahkan dari kehidupan siswa, namun sekaligus menghadirkan tantangan baru bagi lembaga pendidikan Islam dalam menjalankan peran pembentukan karakter. Penelitian ini bertujuan untuk mengkaji strategi yang diterapkan oleh lembaga pendidikan Islam dalam membentuk karakter siswa di era digital, serta mengevaluasi efektivitasnya dalam menghadapi tantangan zaman. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi pustaka sebagai teknik pengumpulan data utama. Hasil kajian menunjukkan bahwa strategi yang diterapkan meliputi integrasi pendidikan digital Islami, model keteladanan guru, penerapan teknologi dalam pembelajaran nilai-nilai keislaman, pemberdayaan kegiatan keagamaan berbasis digital, serta penguatan peran kontrol dan pendampingan oleh orang tua dan guru. Meskipun beberapa lembaga berhasil mengimplementasikan strategi tersebut secara efektif, namun hambatan seperti kurangnya literasi digital, pengawasan yang lemah, serta keterbatasan sumber daya masih menjadi tantangan signifikan. Penelitian ini merekomendasikan pentingnya kolaborasi antara lembaga pendidikan, keluarga, dan masyarakat dalam menyusun kebijakan dan inovasi pembentukan karakter yang sesuai dengan perkembangan teknologi. Temuan ini diharapkan dapat menjadi kontribusi dalam penguatan sistem pendidikan Islam yang responsif terhadap dinamika era digital.